2016
DOI: 10.1002/arp.1535
|View full text |Cite
|
Sign up to set email alerts
|

Slingram EMI Devices for Characterizing Resistive Features Using Apparent Conductivity Measurements: check of the DualEM‐421S Instrument and Field Tests

Abstract: International audienceThis article addresses the characterization of resistive archaeological targets and near surface structures by electromagnetic induction (EMI). It presents tests achieved with the DualEM-421S instrument (Dualem Inc., Milton, Canada) in order to be able to quantitatively compare these measurements to the standard technique of direct-current (d.c.) resistivity. The test was done over the Gallo-roman site of Vieil-Evreux in Normandy, France and one-dimensional (1D) and three-dimensional (3D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Given that any electromagnetic (EM) method in the low frequency range [16] is diffusive and integrates a large volume based on the footprint of the system, this approach will inevitably smoothen out real soil structures. A few authors have suggested to perform a full inversion of the EMI data without assuming the LIN approximation [29][30][31], but it is our impression that this is not common practice. For airborne instruments of a similar type, the industry standard has been to perform a full processing and inversion of the data [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Given that any electromagnetic (EM) method in the low frequency range [16] is diffusive and integrates a large volume based on the footprint of the system, this approach will inevitably smoothen out real soil structures. A few authors have suggested to perform a full inversion of the EMI data without assuming the LIN approximation [29][30][31], but it is our impression that this is not common practice. For airborne instruments of a similar type, the industry standard has been to perform a full processing and inversion of the data [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…During the last forty years, archaeologists have disagreed about the identification of the site, referred to in ancient literary sources as Forentum, and possibly situated in the current towns of Forenza or Lavello. Archaeological discoveries during the past thirty years seem to confirm that Lavello is the Samnitic settlement cited by Livius (9.20.9) and Diodorus Syculus (19,65,7) as the site conquered by the Romans in 318 or 315 BC. In particular, the hill of Gravetta is one of the most interesting and important places for understanding the transition from the Daunii civilization (which inhabited northern Apulia before the arrival of the Romans) to the Roman domination of the territory, with the delicate intermediate Samnitic phase between the fourth and third century BC.…”
Section: Archaeological Contextmentioning
confidence: 68%
“…The integration of different geophysical techniques is key for the success of geophysical techniques applied in archaeological fields [19]. There is a large number of documented examples of the integration of MAG and GPR, where MAG is used to give a large-scale reconstruction of the anomalies related to archaeological features, while GPR is often applied to obtain details of the most interesting anomalies.…”
Section: Geophysical Techniques For Archaeological Issuesmentioning
confidence: 99%
“…As expected, anomalies corresponding to resistive features are less marked and readable with this method than with DC measurements (Dabas et al . ); however, it is of value to confirm the DC resistivity results through independent measurements.…”
Section: Introductionmentioning
confidence: 79%